Article Review : Analysis of the Development of Integrated Teaching Materials of Qur'anic Verses in Science Learning - kholila, azhari (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2023)
Teaching materials are very important for students to help students in understanding the subject matter. Good teaching materials should not only contain knowledge, but also contain spiritual, social, and emotional intelligence. For this reason, it is necessary to conduct research related to the development of teaching materials that are integrated verses of the Qur'an. The method used in this study is the literature review method In this study, researchers reviewed relevant online journals related to the development of integrated teaching materials for Qur'anic verses in science learning. Articles were analyzed in the 2017-2023 timeframe. This study used data obtained from reputable online journal articles published on the internet with a period of 2017-2023. Journal search using Google Scholar database with medium and high quality by entering the keywords